African Perspectives of Research in Teaching & Learning 3 (1): (2019) - Wadesango, Newman editor in chief (My University, 2019)
Refer to the document
APORTAL journal 3 (1): (2019)
APORTAL completed issue 3 (1): (2019)
Keywords: School-based assessment; Total quality management; Internships; Knowledge based economy; Clothing curriculum industry; Carbon footprint; Distance education; Infant education; Private tuition; Quality education; Digital learning system; Vocational evaluation; Total quality management; Internship programs; Knowledge economy; Distance education; Education, Preschool; Total quality management in higher education